Stress and burnout syndrome in teachers – review of the literature - Maciejewska, Martyna; Janik-Fuks, Inga; Wilczyńska, Agnieszka; Wawryków, Agata; Stecko, Monika; Fabian-Danielewska, Anna; Korabiusz, Katarzyna (Journal of Education, Health and Sport, 2019)
Teachers belong to professions particularly vulnerable to burnout. Due to level of teacher’s legal and social responsibility, and impact they have on students, this occupational group is under constant research interest about burnout and coping with stress. Many analyzes indicate connection between individual differences (coping style, emotional intelligence), working conditions, and level of burnout. This article provides review of this research.